2013
DOI: 10.1515/ijnes-2012-0005
|View full text |Cite
|
Sign up to set email alerts
|

Educating DNP Students about Critical Appraisal and Knowledge Translation

Abstract: Consumers expect that health care providers will use the best evidence when assisting them in making decisions about treatment options. Nurses at all educational levels report that they lack knowledge to critically appraise research studies and the skills to effectively implement evidence-based practice (EBP) in their clinical settings. Organizational culture and management support of innovation are critical factors in the adoption of EBP. Doctor of Nursing Practice (DNP) graduates can have a pivotal role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…EBP curricula have traditionally been framed around the steps utilized in the EBP process; development of the population, intervention, comparison, outcome (PICO) question, literature searches, critical appraisal of research evidence, synthesis of findings, development of guidelines for clinical practice and knowledge translation strategies (Cullen, Titler, & Rempel, ; Hart et al., ; Jones, Crookes, & Johnson, ; Keib, Cailor, Kiersma, & Chen, ; Krainovich‐Miller, Haber, Yost, & Jacobs, ; Moore & Watters, ; Rojjanasrirat & Rice, ; Singleton, ). Assignments have included development of a PICO question and search strategy for a topic in the student's clinical area of focus, and completion of a critical review and synthesis of five to six research articles on their topic or a systematic review using the Joanna Briggs Institute model by student teams (Aromataris & Munn, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…EBP curricula have traditionally been framed around the steps utilized in the EBP process; development of the population, intervention, comparison, outcome (PICO) question, literature searches, critical appraisal of research evidence, synthesis of findings, development of guidelines for clinical practice and knowledge translation strategies (Cullen, Titler, & Rempel, ; Hart et al., ; Jones, Crookes, & Johnson, ; Keib, Cailor, Kiersma, & Chen, ; Krainovich‐Miller, Haber, Yost, & Jacobs, ; Moore & Watters, ; Rojjanasrirat & Rice, ; Singleton, ). Assignments have included development of a PICO question and search strategy for a topic in the student's clinical area of focus, and completion of a critical review and synthesis of five to six research articles on their topic or a systematic review using the Joanna Briggs Institute model by student teams (Aromataris & Munn, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assignments have included development of a PICO question and search strategy for a topic in the student's clinical area of focus, and completion of a critical review and synthesis of five to six research articles on their topic or a systematic review using the Joanna Briggs Institute model by student teams (Aromataris & Munn, ). Other assignments can include a critique of a systematic review using the PRISMA guidelines (Liberati et al., ) or a CPG using the AGREE instrument (AGREE Next Steps Consortium, ) or a proposal for a small test of change based on the evidence and guided by the Institute for Healthcare Improvement's (Ogrinc et al., ) Plan‐Do‐Study‐Act model (Jones et al., ; Keib et al., ; Krainovich‐Miller et al., ; Moore & Watters, ; Rojjanasrirat & Rice, ; Singleton, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is part of a range of critical assessment skills programs (CASP) currently available to assess evidence and incorporate it into practice (www.casp-uk.net) (Moore & Watters, 2013). The REA method offered a practical approach that typically takes approximately three months to complete and used a systematic method to review and appraise the selected literature.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Knowledge, skills, attitudes and practice are the keystone of implementing EBP [10,17]. Findings from previous studies indicated that nurses' knowledge, attitudes and beliefs about EBP can play a crucial role to the extent to which EBP is implemented [13,14,18]. Consequently, Knowledge, attitudes can potentially predict future behavior in regard to EBP implementation [1,9].…”
Section: Introductionmentioning
confidence: 99%